2017
DOI: 10.1128/jcm.02562-16
|View full text |Cite
|
Sign up to set email alerts
|

Update on Malaria Diagnostics and Test Utilization

Abstract: Malaria is a potentially life-threatening disease requiring rapid diagnosis and treatment. Although microscopic examination of thick and thin blood films remains the gold standard for laboratory diagnosis, rapid antigen tests and nucleic acid amplification methods may also play a useful role in detection of acute infection. This review discusses the advantages and disadvantages of the commonly used diagnostic methods and provides important practice points for optimal malaria test utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
148
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(153 citation statements)
references
References 13 publications
0
148
0
5
Order By: Relevance
“…The stability of the impregnated anti-bodies, product design and quality, transport, storage and handling conditions as well as the evolving HRP2 gene deletions as being continually reported [20,21] could explain the apparent difference in the performance of the HRP2-based RDTs. Many studies have also reported inherent inability of the RDTs to detect malaria positive cases at low parasite densities [1,22].…”
Section: Discussionmentioning
confidence: 99%
“…The stability of the impregnated anti-bodies, product design and quality, transport, storage and handling conditions as well as the evolving HRP2 gene deletions as being continually reported [20,21] could explain the apparent difference in the performance of the HRP2-based RDTs. Many studies have also reported inherent inability of the RDTs to detect malaria positive cases at low parasite densities [1,22].…”
Section: Discussionmentioning
confidence: 99%
“…DNA-based diagnostics, also referred to as Nucleic Acid Amplification Tests (NAATs), such as DNA/RNA hybridization, conventional and real-time PCR, loopmediated isothermal amplification (LAMP), nucleic acid sequence-based amplification (NASBA) and others can potentially fill this gap by providing a sensitive and accurate identification of multiple Plasmodium species [10,13]. DNA-based malaria assays in general, and PCR in particular, are significantly more sensitive than microscopy and RDTs.…”
Section: Introductionmentioning
confidence: 99%
“…DNA-based malaria assays in general, and PCR in particular, are significantly more sensitive than microscopy and RDTs. Limit of detection (LOD) for PCR is typically 1-5 parasites/µL [13][14][15][16][17] compared to 50-500 parasites/µL for microscopy [13,14,18] and more than 100 parasites/µL for RDT's [14,19]. Depending on the assay, PCR can be used for accurate species identification, detection of mixed infections, and parasite density estimation [20].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the versatility and wide adoption of manual microscopy [4] and its role in direct visual identification of parasites [5], it remains a WHO gold standard for numerous diseases [1]. Despite technological advancements in related fields, the practice of conventional manual microscopy has remained largely unchanged over the last half century and suffers from several drawbacks.…”
Section: Introductionmentioning
confidence: 99%